CETP inhibitor evacetrapib enters mouse brain tissue - Phénix, Jasmine; Côté, Jonathan; Dieme, Denis; Recinto, Sherilyn J.; Oestereich, Felix; Efrem, Sasen; Haddad, Sami; Bouchard, Michèle; Munter, Lisa Marie (Frontiers in Pharmacology, 2023)
High levels of plasma cholesterol, especially high levels of low-density lipoprotein-cholesterol (LDL-C), have been associated with an increased risk of Alzheimer's disease. The cholesteryl ester transfer protein (CETP) in plasma distributes cholesteryl esters between lipoproteins and increases LDL-C in plasma. Epidemiologically, decreased CETP activity has been associated with sustained cognitive performance during aging, longevity, and a lower risk of Alzheimer's disease. Thus, pharmacological CETP inhibitors could potentially be repurposed for the treatment of Alzheimer's disease as they are safe and effective at lowering CETP activity and LDL-C. While CETP is mostly expressed by the liver and secreted into the bloodstream, CETP is also expressed by astrocytes in the brain. It is therefore important to determine if CETP inhibitors can enter the brain. Here, we describe pharmacokinetic parameters of the CETP inhibitor evacetrapib in plasma, liver, and brain tissues in CETP transgenic mice. We show that evacetrapib crosses the blood-brain barrier and is detectable in brain tissue 0.5 h after a 40 mg/kg i.v. injection in a nonlinear function. We conclude that evacetrapib may prove to be a good candidate to treat CETP-mediated cholesterol dysregulation in Alzheimer's disease.